In vitro Binding Interaction of Isoxazoline Derivative with BSA: Equilibrium, FT-IR, Acoustical and Molecular Modeling Study - Pisudde, Ajay Madhukarrao; Tekade, Pradip Vitthalrao; Thakare, Shrikant Bandupant (Orbital: The Electronic Journal of Chemistry, 2020)
The present study showed the binding interaction of 2-(4,5-Dihydro-1,2-oxazol-5-yl)-phenol-N-methylaniline (2DHOPNA) with BSA in 1,4-dioxane, DMSO and DMF by equilibrium dialysis, FT-IR, acoustical at physiological pH and its molecular modeling study. Findings were interpreted by scatchard plot which showed an increase in association constants with increasing temperature and concentrations of the 2DHOPNA. It is seen that, the binding supposed to be more significant in 1,4-dioxane than DMSO and DMF. Thermodynamic parameters are also determined for the binding interaction of 2DHOPNA with BSA. Values of Gibb’s free energy (∆G), enthalpy (∆H) and entropy (∆S) were calculated by using van’t Hoff equation. The positive values of ∆H and ∆S showed exothermic interaction between 2DHOPNA and BSA. Similarly, negative ∆G showed the spontaneity of the binding process. ∆G becomes more negative with increase in temperature, indicated feasibility of the binding interaction at high temperature. Molecular modeling confirmed the binding interaction having energy of -210.13. DOI: http://dx.doi.org/10.17807/orbital.v12i3.1450